2014
DOI: 10.1007/s40477-014-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of ecographic classification for seroma after laparoscopic ventral hernia repair

Abstract: Introduction Seroma is one of the most common complications after laparoscopic ventral hernia repair (LVHR), even if the incidence brought in literature is varying because definition and criterions of evaluation employed in the different studies are not always the same. This study proposes a classification for seroma after LVHR based on ultrasound findings, useful for an assessment of this complication. Materials and methods On 93 patients submitted to LVHR an ultrasound of the abdominal wall after 3, 7, 15, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This collection can be regressed or persistent. [17][18][19][20] Figure 6. A 27-year-old male patient presents with swelling of the bilateral scrotum and left lower abdomen, accompanied by persistent dull pain.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This collection can be regressed or persistent. [17][18][19][20] Figure 6. A 27-year-old male patient presents with swelling of the bilateral scrotum and left lower abdomen, accompanied by persistent dull pain.…”
Section: Managementmentioning
confidence: 99%
“…Note that if the processus vaginalis is not ligation, it can lead to postoperative fluid collection (Figure 9). This collection can be regressed or persistent 17–20 …”
Section: Managementmentioning
confidence: 99%
“…The most common complication after mesh implantation is seroma. After surgery, almost all patients have seroma around the surgery site but only around 8% of them is clinical significantly [57]. Patients usually feel pain for some time.…”
Section: Complicationmentioning
confidence: 99%
“…[8] Surgical intervention may be necessary after an intractable seroma forms a shell. [9] In recent years, several studies have shown that negative pressure drainage in the preperitoneal space during TAPP and TEP surgery can significantly reduce postoperative seroma. By contrast, other studies have shown that drainage has no significant effect on their occurrence, but may be related to the type of hernia, surgical skills, and heterogeneity of patients' basic conditions.…”
Section: Introductionmentioning
confidence: 99%